Pengaruh Current Ratio, Debt To Asset Ratio, Net Profit Margin Dan Total Asset Turnover Terhadap Harga Saham: (Studi Empiris pada Perusahaan Sub Sektor Konstruksi dan Bangunan yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Syifa Fauziyah; Sugeng Priyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of Current Ratio, Debt to Asset Ratio, Net Profit Margin and Total Asset Turnover on Stock Price on Construction and Building Sub-Sector Companies Listed on the Indonesia Stock Exchange Period 2018-2022. This type of research is quantitative research. The sampling technique in this research is the purposive sampling technique to obtain as many as 16 samples of companies from 26 companies. This study used secondary data, namely the annual financial statements. The analysis technique uses multiple linear regression analysis using the Statistical Program for Social Science (SPSS) version 25 program. The results showed that net profit margin had an effect on stock price, meanwhile current ratio, debt to asset ratio and total asset turnover had no impact on stock price.